HUBUNGAN PERSEPSI REMAJA TENTANG KEBIASAAN MAKAN DENGAN STATUS OBESITAS DI SMK TRISULA 1 DEPOK SLEMAN YOGYAKARTA - Siti Uswatun Chasanah; Eva Runi Khristiani (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2018)
Background: The eating habits of junk food among teenagers and its effects on their health. This study found the diet of teenagers who are suspended by junk food alias junk food for lack of essential vitamins because it causes various health problems in the future. This is in accordance with the results of the preliminary study at SMK Trisula 1 Depok Sleman Yogyakarta where there are some teenagers who do not know about unhealthy eating habits with nutritional status.Objective: To know relation of adolescent perception about healthy eating habits with nutritional status at SMK Trisula 1 Depok Sleman Yogyakarta. Methods: The type of research used is descriptive analytic using cross sectional approach. Number of respondents. Methods data using questionnaires, weight size, height, univariate bivariate.Result: Adolescent perception about unhealthy eating habits at SMK Trisula 1 Depok Sleman Yogyakarta as a whole with adolescent perception rate of 14 people (24,1%), teenage score 18 people (31,0%), and adolescent perception less 25 people (44.8%). Conclusion: Overall perception of adolescent about unhealthy eating habits with nutritional status in SMK Trisula 1 Depok Sleman Yogyakarta seen at frequency of adolescent perception about healthy healthy eating habits do not have less adolescent perception leve